Amral's Cavaliers: The Crowd Pleasers and Dynamic Superstars - Unknown (Sunday Guardian)
The Amral's Trinidad Cavaliers have performed and received standing ovations and encores both in Canada and the United States during the past four years. The Cavaliers tour, described as the most fantastic and ambitious ever undertaken included East Africa, Pakistan, India, Malaysia and Europe.
Keywords: Steel bands (Music) -- Trinidad and Tobago; Music -- Performance; Steel band music -- Trinidad and Tobago